„Levél a bennünk élő gyermekhez” – gyógyító írás, belső gyermek, irodalom - Györgyi VÁRADI-KUSZTOS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Letter to the Inner Child – Expressive Writing in Literary Context. The paradigm of expressive writing and its well-known benefits in the field of improving mental health are well known since the end of the twentieth century. In my essay, I would like to explain the connections of this approach with the highly influential works of John Bradshaw as well as the concept of self-healing through expressive writing with the help of the example found in the classical Hungarian epistolary novel Fanni hagyományai.